Testing the Effectiveness of the Cantol Roudhoh Method in Early Reading Acquisition: A Quasi-Experimental Study Among Islamic Kindergarten Learners - Ulfah Amini; Eti Nurhayati; Dian Widiantari (International Journal of Learning Reformation in Elementary Education, 2026)
Early reading acquisition remains a persistent challenge in early childhood education, particularly in identifying instructional strategies that align with the cognitive and developmental characteristics of young learners. Although the Cantol Roudhoh method has been widely applied in Indonesian Islamic kindergarten settings, empirical evidence supporting its effectiveness through rigorous quantitative analysis remains limited. This study aimed to examine the effectiveness of the Cantol Roudhoh method in improving early reading skills among Group A learners in an Islamic kindergarten in Cirebon Regency, Indonesia. A quasi-experimental design using a one-group pretest–posttest approach was employed. The participants consisted of 25 children selected through saturated sampling. Data were collected using a structured early reading assessment instrument that had undergone expert validation and reliability testing, yielding a Cronbach’s Alpha coefficient exceeding 0.70. Descriptive analysis revealed a notable increase in students’ reading performance, with the mean score rising from 7.44 in the pretest to 17.30 in the posttest. Inferential statistical analysis further confirmed a statistically significant difference between the two measurements (t = 14.687, p < 0.05). These findings indicate that the Cantol Roudhoh method effectively enhances early reading acquisition through multisensory and associative learning processes. The study provides empirical support for the integration of structured multisensory instructional strategies in Islamic early childhood education and contributes to the growing body of literature on effective approaches to early literacy development.